2017
DOI: 10.1190/tle36120995.1
|View full text |Cite
|
Sign up to set email alerts
|

4D DAS VSP as a tool for frequent seismic monitoring in deep water

Abstract: Thanks to its relatively low cost, time-lapse vertical seismic profiling (VSP) with distributed acoustic sensing (DAS) is an attractive proposition for frequent seismic monitoring around production and injection wells, aimed at production optimization in complex deepwater fields. We demonstrate that 4D DAS VSP provides sufficient data quality for reservoir monitoring in deep water, with a high value-to-investment ratio. 4D quality and image extent can be enhanced through well-executed acquisition and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…One of the first published examples is from 2011, in a deep onshore well in Pinedale, Canada [ 56 ]. A large variety of deployments in different environments, such as hydrocarbon reservoirs, glaciers, geothermal fields, and carbon sequestration sites, have been reported since then [ 34 , 36 , 69 , 70 , 71 ]. Figure 3 shows a DAS-VSP record from 2011 and its excellent match to a downhole geophone survey conducted a year earlier.…”
Section: Vertical Seismic Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first published examples is from 2011, in a deep onshore well in Pinedale, Canada [ 56 ]. A large variety of deployments in different environments, such as hydrocarbon reservoirs, glaciers, geothermal fields, and carbon sequestration sites, have been reported since then [ 34 , 36 , 69 , 70 , 71 ]. Figure 3 shows a DAS-VSP record from 2011 and its excellent match to a downhole geophone survey conducted a year earlier.…”
Section: Vertical Seismic Profilingmentioning
confidence: 99%
“…DAS-VSP can also be used to track subsurface changes in hydrocarbon reservoirs [ 36 , 81 ]. Seismic properties may vary due to the stimulation of unconventional reservoirs [ 89 , 90 , 91 ] and production, primarily important in conventional ones [ 36 ]. For example, [ 91 , 92 ] show how 4-D DAS-VSP acquired in a deviated well can delineate seismic signatures related to fractures opening during stimulation.…”
Section: Vertical Seismic Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Barberan et al (2012), Didraga (2015), and Daley et al (2016) have demonstrated that fibers deployed on tubing can be used to acquire offset and walk-away VSP data. Mateeva et al (2017) demonstrated the feasibility of using DAS on tubing installation for 4D VSP.…”
Section: Introductionmentioning
confidence: 97%
“…Several field experiments of VSP using DAS measurement (DAS-VSP) in recent years have revealed the efficiency and effectiveness of the technology for future subsurface monitoring (e.g. Mateeva et al 2017).…”
mentioning
confidence: 99%